Convective heat transfer in a nanofluid-saturated porous cavity with the effects of various aspect ratios and thermal radiation. (3rd September 2017) - Muthtamilselvan, M.; Sureshkumar, S.
ABSTRACT: This article reports a fundamental numerical study made to understand the effects of aspect ratio and thermal radiation in a porous cavity filled with nanofluid. The vertical walls of the cavity are insulated while the bottom and top horizontal walls are maintained at constant but different temperatures. The governing equations are solved by using a finite volume method (FVM) on a uniformly staggered grid system. The effects of the pertinent parameters, namely, Richardson number, aspect ratio, radiation parameter, Darcy number, and solid volume fraction are investigated in detail. The computational results are presented in the form of isotherm, streamline, midplane velocity, and Nusselt numbers. The effects of solid volume fraction and thermal radiation are not significant for and 0.5. In general, the results indicate that the convective mechanism is suppressed by radiation, which causes a reduction in the overall heat transfer rate. It is also found that the overall heat transfer rate increases with an increase of Darcy number and solid volume fraction in the presence of thermal radiation effect.